Marketing Barriers Facing Developing Country Manufactured Exporters: A Conceptual Note. - Lall, S (1991)
Conventional analysis of exporting, by ignoring information gaps and transaction costs of various kinds, neglects the role of marketing barriers to new entrants. The nature of the barriers vary by industry, and a variety of institutional mechanisms exists for overcoming them. The appropriateness of the mechanism depends on the capabilities and dynamism of the exporter as well as the nature of information required. The role of foreign buyers has received some attention in recent research in the export of simple consumer goods. This note attempts to develop a more general conceptual framework for marketing barriers.